Traumatic decolamientos of the lower femoral epiphysis: regarding the treatment of its sequels, the viciously consolidated decolamientos, in three personal cases - Pedemonte, Pedro V; Bado, José Luis (Cirugía del Uruguay, 2020)
Presented at session 27th August 1937, relator José Luis Bado